Fatty Infiltrate of the Lumbar Multifidus Muscles Predicts Return to Play in Young Athletes With Extension-Based Low Back Pain. Issue 1 (January 2019) - Winslow, John; Getzin, Andrew; Greenberger, Hilary; Silbert, Walter
Abstract : Objective: To evaluate the predictive value of fatty infiltrate of the lumbar multifidus muscles (LMM) for return to play in young athletes with extension-based low back pain (EB LBP). Design: Retrospective cohort study. Setting: Hospital-based sports medicine practice. Patients: Sixty-two athletes, 61.3% female, and 38.7% male, mean age 14.8 years, with a primary complaint of EB LBP who underwent magnetic resonance imaging (MRI); 46.8% had a pars interarticularis stress reaction or fracture and 53.2% were MRI negative. Interventions: A musculoskeletal fellowship-trained radiologist reviewed MRI for all subjects and graded the degree of fatty infiltrate of the LMM, using the Goutallier classification system (GCS), at the L4/L5 and L5/S1 levels. Main Outcome Measure: Days to return to play after first MD visit were correlated with the amount of fatty infiltrate in the LMM measured on MRI for each subject. Results: When the level of fatty infiltrate increased to a 2 or 3 on the GCS (greater than fatty streaks in the muscle), the predicted probability of return to sport decreased significantly. Conclusion: Our study demonstrated that athletes with EB LBP and fatty infiltrate in the LMM had lower odds of return to sport compared with athletes with normal muscle. Level of Evidence: II B. Clinical Relevance: This study provides sports medicine clinicians with a prognostic tool to help manage young athletes with EB LBP. Clinicians can make decisions regarding rehabilitation and return to play based on MRI findings.